Imaging findings of pelvic venous insufficiency in patients with postural orthostatic tachycardia syndrome. (February 2021) - Knuttinen, Martha-Gracia; Zurcher, Kenneth S; Khurana, Neal; Patel, Indravadan; Foxx-Orenstein, Amy; Harris, Lucinda A; Lawrence, Andrew; Aguilar, Francisco; Sichlau, Michael; Smith, B. Holly; Smith, Steven J
Objectives: Some patients with postural orthostatic tachycardia syndrome (POTS) demonstrate improved dysautonomic symptoms following treatment for pelvic venous insufficiency (PVI). This study assessed the prevalence of significant left common iliac vein (LCIV) compression in POTS patients. Methods: Radiologists retrospectively reviewed CT images of pelvic veins for 216 women (191 with POTS and 25 age-comparable controls).Quantitative vascular analysis identified percent-diameter compression of the LCIV by the right common iliac artery. Significant LCIV compression was defined as >50%. Results: Significant LCIV compression was found in 69% (131/191) of females with POTS versus 40% (10/25) in controls. The hypothesis that venous compression and presence of POTS are independent was rejected ( p = .005). Conclusions: Significant LCIV compression was noted in a majority of female POTS patients, suggesting that incidence of iliac venous obstruction may be higher than the general population. Patients with POTS and symptoms of PVI may benefit from assessment for venous outflow obstruction.